Epidural Abscess Related to Brucellar Spondylodiscitis Diagnosis by Polymerase Chain Reaction (PCR) - Costa, M (2019)
The localized forms of brucellosis, particularly osteoarticular, by their symptomatology usually nonspecific, still continue to be a diagnosis challenge, being fundamental to raise a high degree of suspicion based on a careful epidemiological history. The authors describe the case of a 69 year old farmer that was admitted due to an insidious lower back pain with irradiation to the left lower limb accompanied by nocturnal sweating, anorexia and weight loss. The imaging studies revealed a spondylodiscitis in L3-L4 with an associated epidural abscess. The diagnosis of brucellosis was brought on by the occupational exposure to sheep and was confirmed by a positive PCR to Brucella in the product gathered by aspiration from the epidural abscess and also by the serology (ELISA and Rose Bengal). Despite the initial therapy with doxycycline, rifampicin and gentamycin (the last one for 1 week), the patient had a clinical and imagiologic worsening, determining surgical decompression. After the surgery, antiobiotherapy with doxycyline and rifampicin was maintained and a cycle of gentamicin was started, this time for a month, with a favorable clinical evolution.